Hubungan Status Ekonomi dengan Konsumsi Buah, Sayur dan Pengetahuan Gizi Terhadap Status Gizi pada Siswa SMP di Perkotaan dan Pedesaan di Kotamadya Banjarbaru Tahun 2014 - Nany Suryani; Rosihan Anwar; Hesti Kusuma Wardani; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2015)
Fruits and vegetables have a variety of benefits for the body. Unfortunately it is rarely consumed by the majority people in Indonesia especially adolescents category. According to those cases, the objective of this research is knowing the correlation of economic status with fruit, vegetable consumption and nutrition knowledge toward the nutritional status of students in junior high school of urban and sub-urban at Banjarbaru in the year 2014. This research uses an analytical survey with cross sectional approach. This research takes 135 respondents as the sample. Based on the result of statistics testing (mann-whithney statistics testing) shows that there is difference in economic status in Junior High School of urban and sub-urban (p value =0,025, there is difference in fruit consumption in Junior High School of urban and sub-urban (p value =0,022), there is difference in vegetable consumption in Junior High School of urban and sub-urban (p value =0,028), there is no difference in knowledge in Junior High School of urban and sub-urban (p value =0,059) ), there is no difference in nutrition in Junior High School of urban and sub-urban (p value =0,071). The result of statistic testing by using Chi-Square shows that there is a correlation of economic status and fruit consumption (p value =0,000), correlation of economic status and vegetable consumption (p value =0,000), correlation of economic status and nutritional knowledge (p value =0,000), correlation of fruit consumption and nutrition status (p value =0,000), correlation of vegetable consumption and nutrition status (p value =0,000) and correlation of nutritional knowlledge and nutritional status (p value =0,000).